O2-Sensitive Inks for Measuring Total (Aerobic) Viable Count Using Micro-Respirometry - Sean Cross; Dilidaer Yusufu; Christopher O’Rourke; Andrew Mills (Chemosensors)
The popular method of micro-respirometry (μR) for measuring total viable (aerobic) count (TVC) utilises luminescence-based O2 sensors that are difficult to fabricate and therefore expensive. A simple method is described for making inexpensive, ink-based potential substitutes that utilise the same O2-sensitive dyes. The sensitivity of such inks is readily increased by using dyes with a long lifetime in the absence of O2, τo, and/or an ink resin/polymer with a high O2 permeability, Pm(O2). Response modelling of the μR-based TVC system and subsequent testing using a range of O2 sensors of different sensitivity show that there is little to be gained by making the O2 sensor either very sensitive or insensitive, and that the best O2 sensors are dyes such as Pt(II) tetraphenyltetrabenzoporphyrin (PtBP), with τo = ca. 40–50 μs. Further work shows that a simple-to-make PtBP ink can be used as a direct replacement for the expensive O2 sensor used in commercial instruments for measuring TVC based on μR. In addition, the PtBP can be replaced by an even less expensive O2-sensitive dye, Pt(II) meso-tetra(pentafluorophenyl)porphyrin (PtTFPP). The potential use of inexpensive O2-sensitive inks as an alternative to any expensive commercial counterpart based on the same O2-sensitive dye is discussed briefly.